POLA KOMUNIKASI KEPEMIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA - ernita febriyana; Silviana Purwanti; Kheyene Molekandella Boer (Journal Social Politica, 2022)
delivery of leader’s message to his followers requires a profer communication pattern so that the message submitted will be received well by his followers with good effects. the research method used is a qualitative description research method. the focus of the research of this thesis is on leadership patterns of leadership communication chairman of mulawarman university sketsa for 2017/2018 period in increasing members work motivation consist of formal and informal communication patterns in supported by harold lasswell theori. teh result of the research that the chairman of unmul sketsa conduct a formal pattern of communications by conducting general meetings or field necessary, making directions to members, and submitting the result of working better with supplied result. polite before meeting bearucrats, communicating with other organizations or agencies at the event while informal communication patterns are initially reraly used in the process of communication in this organization, especially in the informal communication pattern of the chairman of the sketsa, but the general chairman is aware of the communication process with more care, attention and empowering all members.